Modeling and experiments of energy storage in a packed bed with PCM. (November 2016) - Izquierdo-Barrientos, M.A.; Sobrino, C.; Almendros-Ibáñez, J.A.
Highlights: A model for the charging process of a fixed bed with PCM is proposed. The model assumes that the phase change occurs over a temperature range. The energy stored in the wall is calculated. The non-dimensionalized equations are valid regardless of whether a PCM is present. Abstract: This work presents a numerical and experimental study of the transient response of a packed bed filled with a granular phase change material (PCM). The proposed numerical model accounts for the progressive evolution of the enthalpy with temperature during the phase change rather than using a constant phase change temperature. This temperature-dependent enthalpy is included in the model as an apparent specific heat that is dependent on temperature according to the measurements obtained by differential scanning calorimetry (DSC). The model also includes the energy stored in the wall, which has been shown to have a non-negligible effect in several experimental facilities. The equations presented are non-dimensionalized, which results in the same differential equation system regardless of whether a granular PCM or sensible heat storage material is used. In this manner, the same numerical method can be used in cases with or without a granular PCM. Numerical and experimental results are obtained for a conventional granular material (sand) and two commercial granular PCMs with different phase change temperatures. The numerical and experimental heating results exhibit good agreement, and the energy stored in the wall of the bed represents between 8 and 16% of the energy stored in the granular material.